2013
DOI: 10.1038/ni.2611
|View full text |Cite|
|
Sign up to set email alerts
|

The role of the immune system in governing host-microbe interactions in the intestine

Abstract: The mammalian intestinal tract harbors a diverse community of trillions of microorganisms, which have co-evolved with the host immune system for millions of years. Many of these microorganisms perform functions critical for host physiology, but the host must remain vigilant to control the microbial community so that the symbiotic nature of the relationship is maintained. To facilitate homeostasis, the immune system ensures that the diverse microbial load is tolerated and anatomically contained, while remaining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
223
0
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(238 citation statements)
references
References 105 publications
3
223
0
12
Order By: Relevance
“…The interdependence of the host and the gut microbiome under homeostatic and inflammatory conditions is well established (13,57). We confirmed that the intestinal microbiota composition and activity were dramatically shifted upon DSS treatment (10,21,24).…”
Section: Discussionsupporting
confidence: 67%
“…The interdependence of the host and the gut microbiome under homeostatic and inflammatory conditions is well established (13,57). We confirmed that the intestinal microbiota composition and activity were dramatically shifted upon DSS treatment (10,21,24).…”
Section: Discussionsupporting
confidence: 67%
“…The commensal microbiome also plays an important role in the structural, barrier, immunological and metabolic functions of the intestine; however, a description of the microbiome at various mucosal surfaces is beyond the scope of this article (Brown et al, 2013;Rosenstiel, 2013). The junctions between the epithelial cells, tight and adherens junctions, which join cells to each other at the apical end of the lateral membrane (Schneeberger and Lynch, 2004), play very important roles in the homeostasis of the intestine and the maintenance of mucosal immunity.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with modulation of gut microbiota by external factors, information is limited on how host immunity regulates its gut microbiota Brown et al, 2013). Recent findings suggest an important role for the innate immune system.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, mice deficient in recombination-activating gene 2 (Rag2) or activation-induced cytidine deaminase had increased segmented filamentous bacteria in the small intestine (Suzuki et al, 2004). Both mutations lead to the lack of IgA (immunoglobulin A) in the intestine, which provides 'an immunological buffer' between the host and microbiota (Brown et al, 2013). Besides IgA (Cebra, 1999;Suzuki et al, 2004;Macpherson and Uhr, 2004;Suzuki and Fagarasan, 2008), T-cell-mediated responses are also hypothesized to shape microbiota in the intestine but evidence is scarce.…”
Section: Introductionmentioning
confidence: 99%